Revealing the Philosophy of Starbucks Logo: Semiotic Analysis - Sihombing, Lambok Hermanto; Lestari, Puji (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2022)
Starbucks is among the most recognizable coffee shops in Indonesia. People will recognize Starbucks by looking at the logo on the cup. The logo is essential in conveying the company's image and impression to customers. A brand's logo represents its identity. This study seeks to elucidate the idea behind the Starbucks logo. This research utilizes a qualitative approach. To assist researchers with their analysis, the Semiotics method and the Representation theory from Stuart Hall are implemented in this research. The result indicates that the Starbucks logo reminds us to be good to people and the world.